2014
DOI: 10.3382/ps.2013-03541
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Cyp51A gene and susceptibility to itraconazole in Aspergillus fumigatus isolated from avian farms in France and China

Abstract: Azole resistance in the fungal pathogen Aspergillus fumigatus is an emerging problem and may develop during azole therapy in humans and animals or exposure to azole fungicides in the environment. To assess the potential risk of azole-resistance emergence in avian farms where azole compounds are used for the control of avian mycoses, we conducted a drug susceptibility study including A. fumigatus isolates from birds and avian farms in France and Southern China. A total number of 175 isolates were analyzed: 57 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…The first strain with these mutations to be described was isolated in 2001 from a clinical sample in a Spanish hospital (5). These strains have now been reported in many European countries (6-10, 13, 20, 21), the United States (22), Canada (23), India (15), China (24), and Australia (16). Some authors have reported that these substitutions are not associated with azole resistance (5,25).…”
mentioning
confidence: 99%
“…The first strain with these mutations to be described was isolated in 2001 from a clinical sample in a Spanish hospital (5). These strains have now been reported in many European countries (6-10, 13, 20, 21), the United States (22), Canada (23), India (15), China (24), and Australia (16). Some authors have reported that these substitutions are not associated with azole resistance (5,25).…”
mentioning
confidence: 99%
“…All three cities are located in the east or southeast of China. AT present, the epidemiology of azole resistance in A. fumigatus in different parts of China and its association with azole fungicides in agriculture are still largely unknown since susceptibility testing is not routinely performed in clinical microbiology laboratories and azole-resistant strains have not yet been identified from environmental sources (14). In the present study, we sought to investigate the occurrence and characteristics of azole resistance in clinical and environmental A. fumigatus isolates from different geographic areas in China and explore the genetic relatedness of azole-resistant isolates from China and international collections through putative cell surface protein (CSP) and microsatellite genotyping.…”
mentioning
confidence: 99%
“…Regarding poultry farms, the use of azoles for prophylaxis and treatment of aspergillosis is unusual, owing to concerns regarding the existence of drug residues in meat and the expense. However, unusual circumstances could lead to antifungal prophylaxis on farms [82]. On the other hand, the use of azoles for decontaminating bedding and environmental disinfection is common [51,70,71,[82][83][84][85].…”
Section: Aspergillosis In Avian Speciesmentioning
confidence: 99%
“…Regarding avian species, despite the importance of aspergillosis in these animals, there are few studies evaluating resistance or cryptic species. The majority of those reports are in poultry, and the rate of resistance is considered low thus far [70,82,108,109]. On the other hand, a few reports on Aspergillus susceptibility studies isolated from captive wild birds are described [110,111].…”
Section: Aspergillus Azole Resistancementioning
confidence: 99%